The Influence of Basic Life Support Training on the Knowledge, Attitude and Practice of Non-Medical Personnel in Kartika Husada Clinic, Malang East Java, Indonesia - Ambarika, Rahmania; Wihatno, Elvianto; Anggraini, Novita Ana; Wahid, Abdurahman; Sandy-Hodgetts, Kylie (Malaysian Journal of Medical Research (MJMR), 2023)
Cardiac arrest refers to the sudden and abrupt loss of heart function. There are many cardiac arrests and only a 14% survival rate due to delays in patient reporting and in giving Basic Life Support (BLS). The purpose of this study was to determine how basic life support (BLS) training affected the knowledge, attitudes, and BLS practices of lay officers at the Kartika Husada Clinic in Malang. The research design was one group pretest and post-test. The population was all non-medical officers at the Kartika Husada Malang Clinic, totaling 17 people. The sample was 17 respondents using a purposive sampling technique. The research was conducted on 16-17 February 2022 at the Kartika Husada Clinic, Malang. The variables of this study were the knowledge, attitudes and practices of non-medical staff at the Kartika Husada Malang Clinic after providing BLS training interventions. The statistical test used Wilcoxon and the results show that the knowledge with p-value of 0.02; attitude with p-value of 0.03; and practice p-value of 0.01. These three variables show the effect of BLS training on the knowledge, attitudes and practices of non-medical staff at Kartika Husada Malang Inpatient Clinic. This result was motivated by exposure to previous information, education level, and body mass index. After this research was conducted and provided training to non-medical staff, it could be applied if they find a heart attack case at the Kartika Husada Clinic.